ADVOKASI GUSDUR TERKAIT AGAMA MINORITAS (PERSPEKTIF MULTIKULTURALISME): (PERSPEKTIF MULTIKULTURALISME) - Sari, Nova Puspita; Firmansyah, Muhammad; Hidayat, Lutfi Alvian (Jurnal SUARGA: Studi Keberagamaan dan Keberagaman, 2025)
Advocacy carried out by Abdurrahman Wahid (Gus Dur) for minority religions is one of the real manifestations of the struggle for multiculturalism in Indonesia. As a country with religious, cultural, and ethnic diversity, Indonesia often faces challenges in the form of discrimination against minority groups. This creates social inequality that threatens harmony in a pluralistic society. This study aims to analyze how Gus Dur's views and advocacy in fighting for the rights of minority religions through a multicultural perspective, with a focus on the application of the values ​​of equality, tolerance, and pluralism in the socio-political context of Indonesia. This study uses a qualitative approach with descriptive analysis. Data were collected through literature studies and documentation from various sources, including speeches, writings, and policies initiated by Gus Dur during his lifetime, as well as academic literature relevant to multiculturalism. The analysis process aims to see advocation of gusdur in multiculturalism. The results of the study show that Gus Dur consistently advocated for full recognition of the rights of minority religions by opposing discrimination and prioritizing humanitarian values ​​as the foundation of national life. His multicultural views are reflected in efforts to create social harmony through a dialogical approach and inclusive policies. These findings emphasize the importance of a multicultural approach as an effective strategy to address the challenges of diversity and strengthen social justice in Indonesia. This study contributes to the discourse on pluralism and public policies that support the protection of rights for all groups in society, including religious minorities.